An investigation of the unstable phenomena of natural convection in parallel square plates by multi-GPU implementation. (2nd January 2017) - Fu, Wu-Shung; Wang, Wei-Hsiang; Li, Chung-Gang; Tsubokura, Makoto
ABSTRACT: Unstable phenomena induced by natural convection of parallel square plates are investigated numerically. The geometry belongs to the open boundary problem, and the compressibility of fluids is taken into consideration. The absorbing boundary condition and modified local one-dimensional inviscid relation method are adopted for open boundaries. Numerical methods of the Roe scheme, preconditioning, and dual time stepping matching the data-parallel lower-upper relaxation method are coordinated with multi-GPU implementation. Unstable phenomena of natural convection caused by the buoyancy force can be observed. Present results have good agreement with the experimental results in the overlap range of the existing study.